Brief Mindfulness-Based Intervention (Brief MBI) dalam Mengurangi Impulsivitas Reaksi Emosi Pada Orang dengan Bipolar (ODB) - Ni Luh Kade Nadia Rastafary; Marselius Sampe Tondok (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to see the effect of the Brief Mindfulness-Based Intervention (Brief MBI) to reduce the impulsivity of emotional reactions in people with bipolar disorder (ODB). This study uses a mixed method design with interviews, observations, Mood Disorder Questionnaire (MDQ), Decision Tree for Elevated or Expansive Mood, Decision Tree for Depressed Mood and Graphic Tests (WZT, DAP, BAUM, HTP). The participant is a 27-year-old woman and has been diagnosed with Bipolar disorder. The symptoms that appear are difficulty in regulating mood to the point of disrupting daily routines, periods of excessive mood elevation and periods of significant mood decline. The MBI Brief is held in four sessions, each session lasting two hours. The results of the intervention showed that the participants experienced an increase in the ability to control themselves before displaying the emotional reactions they felt.